Types and Meanings of Idiomatic Expressions in Justin Bieber’s Songs - Azmi Randu Farhani; Ria Saraswati (Jurnal Pendidikan dan Sastra Inggris, 2025)
This research delves into the linguistic intricacies of Justin Bieber's Justice album, employing a comprehensive documentation analysis approach. The study aims to identify and categorize idiomatic expressions within the album, utilizing Fernando's (1996) typology, and subsequently, to explore the associated meanings through Leech's (1981) semantic framework. The research spans a ten-month period from March to December 2023, with a primary focus on idioms in the song lyrics. Through meticulous examination of a diverse range of idiomatic expressions, including pure idioms, semi-idioms, and literal idioms, the study unveils the prevalence and diversity of figurative language in Bieber's songwriting. Furthermore, an in-depth analysis of idioms' meanings reveals a predominance of connotative meanings, underscoring the album's richness in emotional and contextual nuances. The research not only advances our understanding of idiomatic expressions but also contributes to broader linguistic and pedagogical contexts. The findings offer valuable insights for English language learners, educators, and researchers, emphasizing the incorporation of contemporary music in language acquisition and the nuanced exploration of meaning types within idioms.